Laminated film
Patent Information
- Application Number
- JP2024220249
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-01-12
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-01-05
AI Technical Summary
【0018】 本発明者らは、かかる技術によって、環境に配慮しつつ、無機薄膜層を積層した際に、包装材料に求められるバリア性や接着性等の必要性能を有するための、積層フィルムを提供することが可能となった。
Smart Images

Figure 2025028241000001 
Figure 2025028241000002 
Figure 2025028241000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate film, and more specifically to a gas barrier laminate film that imposes a small environmental load during production and disposal, and that combines both excellent gas barrier performance and sufficient adhesive strength between layers for use as a packaging material. [Background technology]
[0002] In recent years, regulations aimed at reducing the use of disposable plastics have been strengthened in Europe and other countries around the world. Behind this lies the growing international awareness of resource circulation and the worsening waste problems in emerging countries. For this reason, there is a demand for environmentally friendly products from the perspective of the 3Rs (recycle, reuse, reduce) for plastic packaging materials required for food, medicines, etc.
[0003] The performance required for the aforementioned environmentally friendly packaging materials includes (1) being made from materials that are easy to recycle, (2) having gas barrier performance that can block various gases and extend the shelf life, and (3) having a laminate structure that has a low environmental impact (for example, not using organic solvents, using only small amounts of materials, and being recyclable by converting them into mono-materials).
[0004] In recent years, the use of polypropylene films has been attracting attention in order to make the above (1) and (3) possible. Polypropylene films are used for a wide range of purposes, such as packaging for food and various other products, electrical insulation, and surface protection films. Polypropylene films are capable of exhibiting high water vapor barrier properties due to their molecular structure. Furthermore, since polypropylene- or polyethylene-based heat seal resins are generally used as sealants to be bonded to the surface substrate film, for example, by using a polypropylene film for the surface substrate and an unstretched polypropylene sheet for the sealant, it is possible to achieve mono-materialization of the entire packaging material while maintaining gas barrier properties, and to design packaging materials that are easy to recycle and are environmentally friendly.
[0005] However, with regard to the gas barrier property of (2) above, although polypropylene film has water vapor barrier property, the value is not sufficient compared to, for example, transparent inorganic vapor-deposited polyester film, which is generally considered to have excellent water vapor barrier property, and there is a problem that the oxygen barrier property is very poor. In response to this, films have been used in which a polymer resin composition, which is generally considered to have a relatively high oxygen barrier property, such as polyvinyl alcohol, ethylene-vinyl alcohol copolymer, polyvinylidene chloride resin, polyacrylonitrile, etc., is laminated on a polypropylene film (for example, see Patent Documents 1 to 3).
[0006] However, the gas barrier coating film made of the above-mentioned polyvinyl alcohol or ethylene vinyl alcohol copolymer polymer resin composition has a high humidity dependency, so that the gas barrier property is reduced under high humidity conditions, and the water vapor barrier property and water-resistant adhesion are not sufficient. Also, polyvinylidene chloride resin and polyacrylonitrile have a low humidity dependency, but have problems in that the water vapor barrier property is not sufficient and there is a high risk of generating harmful substances when disposed of or incinerated.
[0007] Furthermore, all of the above-mentioned barrier coat layers needed to be laminated to a thickness of 1 μm or more in order to achieve sufficient barrier performance. If the barrier coat layer was too thick, it could become a source of impurities during recycling, making recycling itself difficult. It was also not suitable from the perspective of mono-materialization using a single material. Furthermore, there were issues with printing defects due to unevenness and irregularities in the coating during processing such as printing.
[0008] To address these problems, gas barrier laminates are generally used in which a thin metal film made of aluminum or the like or a thin inorganic film made of an inorganic oxide such as silicon oxide or aluminum oxide is formed on the surface of a plastic substrate film such as a polyester film. Among these, those in which a thin inorganic oxide film such as silicon oxide, aluminum oxide, or a mixture thereof is formed are widely used because they do not require the use of aluminum foil, are transparent so that the contents can be confirmed, and furthermore, the formed film is very thin and does not impede recyclability.
[0009] A method has also been disclosed for imparting gas barrier properties to polypropylene films by laminating an inorganic thin film (e.g., Patent Document 4). However, since the molecules of polypropylene films are nonpolar, the surface energy is small, and it has been pointed out that the adhesion is therefore insufficient when processing inorganic thin films.
[0010] In response to this, a method has been disclosed for improving adhesion by controlling the orientation angle of the molecular chains of a polypropylene film (for example, Patent Document 5). However, there is no mention of gas barrier properties or water-resistant adhesion.
[0011] In addition, when forming an inorganic thin film layer, there is a problem not only with adhesion but also with the protruding parts due to surface unevenness, which makes it impossible to form a thin film, resulting in poor barrier properties. On the other hand, biaxially oriented polypropylene film has poor slipperiness due to its excellent flexibility and flatness, and blocking occurs when films stick to each other, so anti-blocking agents are generally added to form surface unevenness. As a result, the uneven surface that is formed makes it difficult to form a thin film by deposition or coating, which leads to problems such as poor barrier properties.
[0012] To address these problems, a method has been disclosed in which the above-mentioned polyvinyl alcohol polymer resin composition is used and an inorganic thin film is laminated thereon to impart gas barrier properties (e.g., Patent Document 5). However, when a polyvinyl alcohol polymer resin composition is used, there is still a risk of poor water-resistant adhesion due to its large humidity dependency. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] JP 2000-52501 A [Patent Document 2] Japanese Patent Application Publication No. 4-359033 [Patent Document 3] JP 2003-231221 A [Patent Document 4] International Publication No. 2017 / 221781 [Patent Document 5] Patent No. 6380381 [Patent Document 6] JP 2020-131674 A Summary of the Invention [Problem to be solved by the invention]
[0014] The barrier properties and adhesive properties were insufficient in the above Patent Documents 1 to 4. Patent Document 5 does not mention barrier properties, and Patent Document 6 does not mention improvement of water-resistant adhesiveness.
[0015] The present invention has been made in view of the above problems in the prior art. In other words, the object of the present invention is to provide a laminate film that can form a laminate structure composed of almost a single resin type that has a low environmental impact, mainly consisting of a polypropylene film, and that, when laminated with an inorganic thin film layer, has the gas barrier properties and adhesive properties required for packaging materials. [Means for solving the problem]
[0016] The present inventors have discovered that by designing a specific laminate film tailored to the required performance, it is possible to provide a film that exhibits good gas barrier properties and adhesive properties when laminated with an inorganic thin film layer, and have thus completed the present invention.
[0017] That is, the present invention comprises the following: 1. A laminate film having a surface layer (B) on at least one side of a base layer (A) mainly composed of a polypropylene-based resin, and further having a coating layer laminated on the surface layer (B), characterized in that the laminate film satisfies the following requirements (I) to (III). (I) When the Martens hardness when the coating layer surface is measured with a test force of 0.1 mN is (a), and the Martens hardness when the coating layer surface is measured with a test force of 7 mN is (b), the relationship (a) / (b) ≦ 7.00 is satisfied. (II) The sum of the maximum peak height (Rp) and the maximum valley depth (Rv) measured on the coating layer side surface by a scanning probe microscope is 30.0 nm or less. (III) Oxygen permeability measured under conditions of 23°C x 65% RH is 100cc / m 2 / day / atm or more, 1200cc / m 2 / day / atm or less. 2. The laminate film according to claim 1, further comprising an inorganic thin film layer laminated on the coating layer of the laminate film. 3. The coating layer has a coating weight of 0.10 g / m 2 More than 1.00g / m 2 3. The laminated film according to claim 1 or 2, characterized in that: 4. A laminate obtained by laminating an olefin-based sealant layer on one side of the laminate film according to any one of 1. to 3. 5. The laminate according to claim 4, characterized in that the laminate has a lamination strength of 1.5 N / 15 mm or more. 6. A packaging material comprising at least one layer of the laminate film according to any one of 1. to 5. Effect of the Invention
[0018] By using this technology, the inventors have been able to provide a laminated film that, when laminated with an inorganic thin film layer, has the necessary properties, such as barrier properties and adhesive properties, required for packaging materials, while being environmentally friendly. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present invention will be described in detail below. A laminate film having a surface layer (B) on at least one surface of a base layer (A) mainly composed of a polypropylene-based resin, and further having a coating layer laminated on the surface layer (B), wherein the laminate film satisfies the following requirements (I) to (III): (I) When the Martens hardness when the coating layer surface is measured with a test force of 0.1 mN is (a), and the Martens hardness when the coating layer surface is measured with a test force of 7 mN is (b), the relationship (a) / (b) ≦ 7.00 is satisfied. (II) The sum of the maximum peak height (Rp) and the maximum valley depth (Rv) measured on the coating layer side surface by a scanning probe microscope is 30.0 nm or less. (III) Oxygen permeability measured under conditions of 23°C x 65% RH is 100cc / m 2 / day / atm or more, 1200cc / m 2 / day / atm or less. Each layer of the laminated film will now be described.
[0020] [Base film layer] (1) Base material layer (A) The base layer (A) mainly composed of a polypropylene-based resin constituting the laminated film of the present invention is preferably a biaxially oriented film, and the polypropylene used in the layer may be a polypropylene copolymerized with 0.5 mol % or less of ethylene and / or an α-olefin having 4 or more carbon atoms. Such copolymerized polypropylene is also included in the polypropylene of the present invention (hereinafter, polypropylene). The copolymerization component is preferably 0.3 mol % or less, more preferably 0.1 mol % or less, and a completely homopolypropylene containing no copolymerization component is most preferred. When ethylene and / or an α-olefin having 4 or more carbon atoms is copolymerized in an amount exceeding 0.5 mol %, the crystallinity and rigidity are too low, and the thermal shrinkage rate at high temperatures may become large. Such resins may be blended and used.
[0021] The mesopentad fraction ([mmmm]%) measured by 13C-NMR, which is an index of stereoregularity of the polypropylene constituting the base layer (A) of the laminated film of the present invention, is preferably 98 to 99.5%, more preferably 98.1% or more, and even more preferably 98.2% or more. If the mesopentad fraction of the polypropylene is small, the elastic modulus will be low and the heat resistance may be insufficient. 99.5% is the practical upper limit.
[0022] The mass average molecular weight (Mw) of the polypropylene constituting the base layer (A) of the laminated film of the present invention is preferably 180,000 to 500,000. If the Mw is less than 180,000, the melt viscosity is low, so the resin is not stable during casting, and film-forming properties may be poor. If the Mw is more than 500,000, the amount of components with a molecular weight of 100,000 or less becomes 35% by mass, and the heat shrinkage rate at high temperatures deteriorates. A more preferred lower limit of Mw is 190,000, even more preferably 200,000, and a more preferred upper limit of Mw is 320,000, even more preferably 300,000, and particularly preferably 250,000.
[0023] The number average molecular weight (Mn) of the polypropylene constituting the base layer (A) of the laminated film of the present invention is preferably 20,000 to 200,000. If it is less than 20,000, the melt viscosity is low, so that the film-forming property may be deteriorated due to instability during casting, whereas if it exceeds 200,000, the heat shrinkage rate at high temperatures is deteriorated. A more preferable lower limit of Mn is 30,000, even more preferably 40,000, and particularly preferably 50,000, and a more preferable upper limit of Mn is 80,000, even more preferably 70,000, and particularly preferably 60,000.
[0024] Furthermore, the Mw / Mn, which is an index of molecular weight distribution, of the polypropylene constituting the base layer (A) is preferably 2.8 to 10, more preferably 2.8 to 8, still more preferably 2.8 to 6, and particularly preferably 2.8 to 5.4. The lower limit is preferably 3 or more, and more preferably 3.3 or more. The molecular weight distribution of polypropylene can be adjusted by polymerizing components of different molecular weights in a series of plants in multiple stages, blending components of different molecular weights offline in a kneader, blending catalysts with different performance properties and polymerizing them, or using a catalyst that can achieve the desired molecular weight distribution.
[0025] When the polypropylene constituting the base layer (A) of the laminated film of the present invention has an Mw / Mn in the range of 2.8 to 5.4, it preferably has a melt flow rate (MFR; 230° C., 2.16 kgf) of 2 g / 10 min to 20 g / 10 min. The lower limit of the MFR of the polypropylene of the base layer (A) is more preferably 3 g / 10 min, further preferably 4 g / 10 min, and particularly preferably 5 g / 10 min. The upper limit of the MFR of the polypropylene constituting the base layer (A) is more preferably 15 g / 10 min, and further preferably 12 g / 10 min. When the Mw / Mn and MFR of the polypropylene constituting the base layer (A) are within this range, the heat shrinkage rate at high temperatures can be kept small, and the adhesion to the cooling roll is good, resulting in excellent film formability.
[0026] (2) Surface layer (B) The polypropylene resin composition constituting the surface layer (B) of the laminated film of the present invention preferably has an MFR of 1.0 g / 10 min to 10.0 g / 10 min. The lower limit of the MFR of the polypropylene resin composition constituting the surface layer (B) is more preferably 2.0 g / 10 min, even more preferably 3.0 g / 10 min, and particularly preferably 4.0 g / 10 min. The upper limit of the MFR of the polypropylene resin composition constituting the surface layer (B) is more preferably 9.0 g / 10 min, even more preferably 8.0 g / 10 min, and particularly preferably 5.5 g / 10 min. Within this range, the film formability is good and the appearance is excellent. If the MFR of the polypropylene resin composition constituting the surface layer (B) is smaller than 1.0 g / 10 min, when the MFR of the polypropylene constituting the base layer (A) is large, the viscosity difference between the base layer (A) and the surface layer (B) becomes large, and unevenness (unevenness of the original roll) is likely to occur during film formation. If the MFR of the polypropylene resin composition constituting the surface layer (B) exceeds 10 g / 10 min, the adhesion to the cooling roll will be poor, air will be entrapped, the smoothness will be poor, and there is a risk that many defects will occur due to this.
[0027] As polypropylene resins with a smaller MFR, polypropylenes copolymerized with ethylene and / or α-olefins having 4 or more carbon atoms can be used. Examples of α-olefins having 4 or more carbon atoms include 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene. In addition, polar maleic acid and the like can be used as other copolymerization components. The total amount of ethylene and / or α-olefins having 4 or more carbon atoms and other copolymerization components is preferably 8.0 mol% or less. If copolymerized in excess of 8.0 mol%, the film may whiten and have a poor appearance, or may become sticky, making film formation difficult.
[0028] These resins may be used in combination of two or more kinds. When blended, each resin may be copolymerized in an amount exceeding 8.0 mol%, but the blend preferably contains 8.0 mol% or less of monomers other than propylene in monomer units. As the polypropylene resin having a larger MFR, the above-mentioned copolymer polypropylene can be used, or a homopolypropylene resin can be used.
[0029] The antiblocking agent can be appropriately selected from inorganic particles such as silica, calcium carbonate, kaolin, and zeolite, and organic particles such as acrylic, polymethacrylic, and polystyrene. Among these, it is particularly preferable to use silica or polymethacrylic particles. The preferred average particle size of the antiblocking agent is 1.0 to 3.0 μm, and more preferably 1.0 to 2.7 μm. The average particle size is measured by taking a photograph with a scanning electron microscope, measuring the Feret's diameter in the horizontal direction using an image analyzer, and expressing the average value. There are no particular limitations on the amount of anti-blocking agent added, so long as the amount added to the surface layer (B) and surface layer (C) is adjusted so that the haze, dynamic friction coefficient, center surface average roughness (SRa), and air release time are within the specified ranges.
[0030] The surface wetting tension of the surface layer (B) of the laminated film of the present invention is preferably 38 mN / m or more. The wetting tension represents the surface tension (mN / m) of a mixed liquid reagent determined to wet the film surface, and is related to the wettability of printing inks and adhesives. If the wetting tension is 38 mN / m or more, the adhesion to the adhesive used for deposition film, coating film, and lamination with other member films is improved. In order to make the wetting tension 38 mN / m or more, additives such as antistatic agents and surfactants are usually used, but these methods have the effect of reducing the surface resistance value, so it is preferable to carry out physicochemical surface treatments such as corona treatment and heat treatment. For example, in the corona treatment, it is preferable to use a preheat roll and a treatment roll and perform discharge in the air.
[0031] (3) Surface layer (C) The laminated film of the present invention may have a surface layer (C) on the opposite side of the substrate layer (A) to the surface layer (B). The surface layer (C) preferably has a center surface average roughness (SRa) of 0.020 μm or more as measured by a three-dimensional surface roughness meter. The center surface average roughness (SRa) of the surface of the surface layer (C) is more preferably 0.022 μm or more, even more preferably 0.025 μm or more, and particularly preferably 0.028 μm or more. If the center surface average roughness (SRa) of the surface of the surface layer (C) is less than 0.020 μm, the surface unevenness is small, and the slipperiness of the film, the air release time between the films, and the blocking resistance are deteriorated. There are several methods for setting the center surface average roughness (SRa) of the surface of the surface layer (C) within the specified range, and it is possible to adjust it by the average particle size and the amount of the antiblocking agent added. The surface layer (C) of the laminate film of the present invention preferably has a center surface average roughness (SRa) of 0.040 μm or less as measured by a three-dimensional roughness meter.
[0032] In addition, the Martens hardness of the surface layer (C) of the laminated film is 270N / mm 2 It is preferable that the load is 275N / mm or more. 2 More preferably, 280N / mm 2 More preferably, 285N / mm 2 That's all. Martens hardness is 270N / mm 2 If the hardness is less than 270N / mm, the surface is soft and the anti-blocking agent sinks into the resin, resulting in poor slipperiness and anti-blocking properties. 2 To achieve a Martens hardness of 0.5% or less, it is preferable to use polypropylene copolymerized with 0.5% or less ethylene and / or an α-olefin having 4 or more carbon atoms, more preferably 0.1% or less, and most preferably a completely homopolypropylene containing no copolymerization components. It is also possible to increase the Martens hardness by setting the mesopentad fraction ([mmmm]%) of the constituent polypropylene to 98% or more and increasing the degree of crystallinity. The Martens hardness of the surface layer (C) of the laminated film is 350N / mm 2 It is preferable that:
[0033] The polypropylene resin used in the present invention is obtained by polymerizing the raw material propylene using a known catalyst such as a Ziegler-Natta catalyst or a metallocene catalyst. Among them, it is preferable to use a Ziegler-Natta catalyst in order to eliminate heterogeneous bonds, and to use a catalyst capable of polymerization with high stereoregularity. As a method for polymerizing the raw material propylene, a known method may be adopted, and examples thereof include a method of polymerizing in an inert solvent such as hexane, heptane, toluene, or xylene, a method of polymerizing in a liquid monomer, a method of adding a catalyst to a gaseous monomer and polymerizing in a gas phase state, or a method of polymerizing by combining these methods.
[0034] The base layer (A) and / or the surface layer (B) and / or the surface layer (C) of the laminated film of the present invention may contain additives or other resins. Examples of additives include antioxidants, ultraviolet absorbers, nucleating agents, adhesives, antifogging agents, flame retardants, inorganic or organic fillers, etc. Examples of other resins include polypropylene resins other than the polypropylene resin used in the present invention, random copolymers which are copolymers of propylene and ethylene and / or α-olefins having 4 or more carbon atoms, and various elastomers. These may be sequentially polymerized using a multi-stage reactor, blended with polypropylene resin using a Henschel mixer, master pellets prepared in advance using a melt kneader may be diluted with polypropylene to a predetermined concentration, or the entire amount may be melt kneaded and used. Furthermore, as long as the object of the present invention is not impaired, corona discharge treatment, glow discharge treatment, flame treatment, surface roughening treatment, and known anchor coat treatment, printing, decoration, etc. may be performed.
[0035] [Coating layer] In the present invention, a coating layer is provided on the surface layer (B). By providing the coating layer, it is possible to suppress the exposure of oligomers and antiblocking materials from the polypropylene resin. Furthermore, when other layers are laminated on the coating layer, it is possible to increase the adhesion between the layers. In particular, in the formation of an inorganic thin film layer, not only adhesion is required, but also there is a problem that a thin film cannot be formed at protruding parts due to surface unevenness, resulting in poor barrier properties. In addition, by using a material having gas barrier properties for the coating layer itself, the gas barrier performance of the laminated film can be greatly improved. Furthermore, the coating layer prevents the intrusion of hot water into the substrate, and as a result, whitening of the film after boiling or retorting can be reduced.
[0036] In the present invention, the coating layer has a coating weight of 0.10 to 1.00 g / m 2 This allows the coating layer to be uniformly controlled during coating, resulting in a film with fewer coating irregularities and defects. Furthermore, the protective layer contributes to suppressing oligomer exposure, stabilizing the haze after retorting. The coating layer is preferably applied in an amount of 0.15 g / m 2 More preferably, 0.2 g / m 2 More preferably, 0.35 g / m 2 or more, preferably 0.9 g / m 2 Less than or equal to 0.8 g / m 2 The coating layer has a coating weight of 1.00 g / m 2 If the thickness of the protective layer exceeds 0.10 g / m, the gas barrier properties improve, but the cohesive force inside the coating layer becomes insufficient and the uniformity of the coating layer also decreases, resulting in unevenness or defects in the appearance of the coat, and insufficient gas barrier properties and adhesiveness. 2 If it is less than this, there is a risk that sufficient gas barrier properties and interlayer adhesion cannot be obtained.
[0037] The resin composition used in the coating layer of the present invention may be one in which a curing agent such as an epoxy, isocyanate, or melamine curing agent is added to a resin such as a urethane, polyester, acrylic, titanium, isocyanate, imine, or polybutadiene curing agent, and may further contain a crosslinking agent such as a silicon-based crosslinking agent, an oxazoline compound, a carbodiimide compound, or an epoxy compound. In particular, the inclusion of a urethane resin is preferable because, in addition to the barrier performance due to the high cohesiveness of the urethane bond itself, the polar group interacts with the inorganic thin film layer, and the film has flexibility due to the presence of amorphous parts, so that damage can be suppressed even when a bending load is applied. In addition, a polyester resin is also preferable because it can be expected to have the same effect. In the present invention, it is preferable to contain a polyurethane having polyester + isocyanate as constituent components, and it is more preferable to add a silicon-based crosslinking agent from the viewpoint of improving water-resistant adhesion.
[0038] (1) Urethane resin From the viewpoint of improving the barrier property by the cohesive force, the urethane resin used in the present invention preferably has a glass transition temperature (Tg) of 100°C or more, more preferably 110°C or more, and even more preferably 120°C or more. However, in order to develop adhesive force, a soft resin having excellent flexibility and a Tg of 100°C or less may be mixed and used. In that case, the addition ratio of the soft resin is preferably within the range of 0 to 80%, more preferably within the range of 10 to 70%, and even more preferably within the range of 20 to 60%. When the addition ratio is within the above range, it is possible to achieve both cohesive force and flexibility, and the barrier property and adhesive property are good. Note that, if the addition ratio exceeds 80%, the film becomes too soft, which may lead to a decrease in barrier performance.
[0039] From the viewpoint of improving gas barrier properties, it is more preferable to use a urethane resin containing an aromatic or araliphatic diisocyanate component as a main constituent component. Among these, it is particularly preferable to contain a metaxylylene diisocyanate component. By using the above resin, the cohesive strength of the urethane bond can be further increased due to the stacking effect between aromatic rings, and as a result, good gas barrier properties can be obtained.
[0040] In the present invention, the proportion of aromatic or araliphatic diisocyanate in the urethane resin is preferably 50 mol% or more (50 to 100 mol%) in 100 mol% of the polyisocyanate component (F). The proportion of the total amount of aromatic or araliphatic diisocyanate is preferably 60 to 100 mol%, more preferably 70 to 100 mol%, and even more preferably 80 to 100 mol%. If the proportion of the total amount of aromatic or araliphatic diisocyanate is less than 50 mol%, good gas barrier properties may not be obtained.
[0041] (2) Silicon-based crosslinking agents In the urethane resin used in the present invention, various crosslinking agents may be blended in order to improve the cohesive strength and the wet heat resistance adhesion of the film, as long as the gas barrier properties are not impaired. Examples of crosslinking agents include silicon-based crosslinking agents, oxazoline compounds, carbodiimide compounds, and epoxy compounds. Among them, silicon-based crosslinking agents are particularly preferred from the viewpoint that the water-resistant adhesion with the inorganic thin film layer can be improved by blending the silicon-based crosslinking agent. In addition, oxazoline compounds, carbodiimide compounds, and epoxy compounds may be used in combination as crosslinking agents.
[0042] As the silicon-based crosslinking agent, a silane coupling agent is preferred from the viewpoint of crosslinking between inorganic and organic substances. As the silane coupling agent, hydrolyzable alkoxysilane compounds, for example, halogen-containing alkoxysilanes (chloro C2-4 alkyl tri C1-4 alkoxysilanes such as 2-chloroethyl trimethoxysilane, 2-chloroethyl triethoxysilane, 3-chloropropyl trimethoxysilane, 3-chloropropyl triethoxysilane, etc.), alkoxysilanes having epoxy groups [2-glycidyloxyethyl trimethoxysilane, 2-glycidyloxyethyl triethoxysilane, 3-glycidyloxypropyl ... trimethoxysilane, glycidyloxy C2-4 alkyl tri C1-4 alkoxysilanes such as 3-glycidyloxypropyl triethoxysilane, glycidyloxy di C2-4 alkyl di C1-4 alkoxysilanes such as 3-glycidyloxypropyl methyl dimethoxysilane and 3-glycidyloxypropyl methyl diethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl triethoxysilane, 3-(3,4-epoxycyclohexyl)propyl (epoxycycloalkyl)C2-4 alkyltriC1-4 alkoxysilanes such as 2-aminoethyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and other amino C2-4 alkyltriC1-4 alkoxysilanes, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, and other amino diC2-4 alkyldiC1-4 alkoxysilanes, 2-[N-(2-aminoethyl)amino (2-amino C2-4 alkyl) amino C2-4 alkyl tri C1-4 alkoxy silanes such as 3-[N-(2-aminoethyl)amino]ethyltrimethoxysilane, 3-[N-(2-aminoethyl)amino]propyltrimethoxysilane, and 3-[N-(2-aminoethyl)amino]propyltriethoxysilane; (amino C2-4 alkyl) amino di C2-4 alkyl di C1-4 alkoxy silanes such as 3-[N-(2-aminoethyl)amino]propylmethyldimethoxysilane and 3-[N-(2-aminoethyl)amino]propylmethyldiethoxysilane;Alkoxysilanes having a mercapto group (mercapto C2-4 alkyl tri C1-4 alkoxysilanes such as 2-mercaptoethyl trimethoxysilane, 3-mercaptopropyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, mercapto di C2-4 alkyl di C1-4 alkoxysilanes such as 3-mercaptopropyl methyl dimethoxysilane, 3-mercaptopropyl methyl diethoxysilane, etc.), alkoxysilanes having a vinyl group (vinyl tri C1-4 alkoxysilanes such as vinyl trimethoxysilane, vinyl triethoxysilane, etc.), ethylene Examples of the silane coupling agents include alkoxysilanes having a reactive unsaturated bond group [(meth)acryloxy C2-4 alkyl tri C1-4 alkoxysilanes such as 2-(meth)acryloxyethyl trimethoxysilane, 2-(meth)acryloxyethyl triethoxysilane, 3-(meth)acryloxypropyl trimethoxysilane, and 3-(meth)acryloxypropyl triethoxysilane, and (meth)acryloxy di C2-4 alkyl di C1-4 alkoxysilanes such as 3-(meth)acryloxypropyl methyl dimethoxysilane and 3-(meth)acryloxypropyl methyl diethoxysilane, etc.]. These silane coupling agents can be used alone or in combination of two or more. Among these silane coupling agents, silane coupling agents having an amino group are preferred.
[0043] The silicon-based crosslinking agent is preferably added in an amount of 0.10 to 3.00% by mass in the coating layer, more preferably 0.15 to 2.75% by mass, and even more preferably 0.20 to 2.50% by mass. The addition of the silane coupling agent promotes the hardening of the film and improves the cohesive force, resulting in a film with excellent water-resistant adhesion, and is also expected to have the effect of preventing the exposure of oligomers. If the amount added exceeds 3.00% by mass, the hardening of the film progresses and the cohesive force improves, but some unreacted portions may be generated, and the adhesion between layers may decrease. On the other hand, if the amount added is less than 0.10% by mass, sufficient cohesive force may not be obtained.
[0044] (3) Polyester resin The polyester resin used in the present invention is produced by polycondensation of a polyvalent carboxylic acid component and a polyhydric alcohol component. The molecular weight of the polyester is not particularly limited as long as it can provide sufficient film toughness, coating suitability, and solvent solubility as a coating material, but is preferably 1000 to 50000 in number average molecular weight, more preferably 1500 to 30000. The functional group at the polyester end is also not particularly limited, and may be an alcohol end, a carboxylic acid end, or both. However, when an isocyanate-based curing agent is used in combination, it is necessary to use a polyester polyol mainly composed of alcohol ends.
[0045] The Tg of the polyester used in the present invention is preferably 15°C or higher. If the temperature is lower than this, the resin becomes sticky after the coating operation, tends to cause blocking, and makes the winding operation after coating difficult. If the Tg is 15°C or lower, it becomes difficult to prevent blocking even under conditions where the pressure near the winding core is high, even with the addition of an anti-blocking agent. The Tg temperature is more preferably 18°C or higher, and even more preferably 25°C or higher.
[0046] The polyester used in the present invention is prepared by polycondensing a polyvalent carboxylic acid component and a polyhydric alcohol component. [Polycarboxylic acid component] The polyvalent carboxylic acid component of the polyester used in the present invention is characterized by containing at least one of ortho-oriented aromatic dicarboxylic acids or their anhydrides. The ortho-orientation improves solubility in solvents, making it possible to uniformly coat the substrate. The uniformly coated protective layer reduces the variation in barrier performance, which ultimately contributes to the suppression of oligo whitening. In addition, the ortho-orientation results in a film with excellent flexibility and improved interfacial adhesion, which reduces damage to the substrate caused by wet heat treatment and leads to the suppression of oligomers. Examples of aromatic polycarboxylic acids or anhydrides thereof in which a carboxylic acid is substituted at the ortho position include orthophthalic acid or anhydride, naphthalene 2,3-dicarboxylic acid or anhydride, naphthalene 1,2-dicarboxylic acid or anhydride, anthraquinone 2,3-dicarboxylic acid or anhydride, and 2,3-anthracene carboxylic acid or anhydride. These compounds may have a substituent at any carbon atom of the aromatic ring. Examples of the substituent include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimide group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, or a naphthyl group. In addition, polyester polyols having a content of 70 to 100 mol% relative to 100 mol% of the total polycarboxylic acid components are particularly preferred because they have a high effect of improving barrier properties and excellent solvent solubility, which is essential for a coating material.
[0047] In the present invention, other polybasic carboxylic acid components may be copolymerized within the range that does not impair the effects of the present invention. Specifically, examples of aliphatic polycarboxylic acids include succinic acid, adipic acid, azelaic acid, sebacic acid, and dodecanedicarboxylic acid; examples of unsaturated bond-containing polycarboxylic acids include maleic anhydride, maleic acid, and fumaric acid; examples of alicyclic polycarboxylic acids include 1,3-cyclopentanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid; examples of aromatic polycarboxylic acids include terephthalic acid, isophthalic acid, pyromellitic acid, trimellitic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyldicarboxylic acid, diphenic acid and its anhydride, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, and anhydrides or ester-forming derivatives of these dicarboxylic acids; p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid, and ester-forming derivatives of these dihydroxycarboxylic acids; and the like, which can be used alone or in a mixture of two or more kinds. Among these, succinic acid, 1,3-cyclopentanedicarboxylic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 1,8-naphthalic acid, and diphenic acid are preferred from the viewpoints of solubility in organic solvents and gas barrier properties.
[0048] [Polyhydric alcohol component] The polyhydric alcohol component of the polyester used in the present invention is not particularly limited as long as it can synthesize a polyester that exhibits gas barrier compensation performance, but it is preferable to contain a polyhydric alcohol component containing at least one selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, cyclohexanedimethanol, and 1,3-bishydroxyethylbenzene. Among them, it is most preferable to use ethylene glycol as the main component, since it is presumed that the smaller the number of carbon atoms between oxygen atoms, the less the molecular chain will be excessively flexible and the less oxygen will permeate.
[0049] In the present invention, it is preferable to use the above-mentioned polyhydric alcohol component, but other polyhydric alcohol components may be copolymerized within the range that does not impair the effects of the present invention. Specifically, the diols include 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, dimethylbutanediol, butylethylpropanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, and tripropylene glycol, and the trihydric or higher alcohols include glycerol, trimethylolpropane, trimethylolethane, tris(2-hydroxyethyl)isocyanurate, 1,2,4-butanetriol, pentaerythritol, and dipentaerythritol. In particular, polyesters using glycerol and tris(2-hydroxyethyl)isocyanurate in combination among trihydric alcohols are particularly preferably used because they have a moderately high crosslinking density due to their branched structure, have good solubility in organic solvents, and have excellent barrier function.
[0050] Examples of catalysts used in the reaction to obtain the polyester of the present invention include tin catalysts such as monobutyltin oxide and dibutyltin oxide, titanium catalysts such as tetra-isopropyl-titanate and tetra-butyl-titanate, and acid catalysts such as zirconia catalysts such as tetra-butyl-zirconate. It is preferable to use the above titanium catalysts such as tetra-isopropyl-titanate and tetra-butyl-titanate, which have high activity in esterification reactions, in combination with the above zirconia catalyst. The amount of the catalyst is 1 to 1000 ppm, more preferably 10 to 100 ppm, based on the total mass of the reaction raw materials used. If the amount is less than 1 ppm, it is difficult to obtain the effect of the catalyst, and if the amount is more than 1000 ppm, a problem of inhibiting the urethane reaction may occur when an isocyanate curing agent is used.
[0051] (4) Isocyanate-based hardener In the present invention, when a polyester resin is used as the main agent of the coating agent constituting the coating layer, it is necessary to use an isocyanate-based curing agent to form a urethane resin. In this case, the coating layer becomes a crosslinked system, which has the advantage of improving heat resistance, abrasion resistance, and rigidity. Therefore, it is easy to use for boiling and retort packaging. On the other hand, there is a problem that the liquid cannot be reused after mixing with the curing agent, and a curing (aging) process is necessary after coating. As an advantage, as a simple overcoat varnish, for example, there is no risk of thickening of the coating liquid, and the coating production is easy to manage, the coating liquid can be diluted and reused, and in addition, a curing process (so-called aging process) is not required. In this case, the end of the polyester used can be polyol, polycarboxylic acid, or a mixture of these two without any problems. On the other hand, since the resin of the coating layer is linear, there are cases where the heat resistance and abrasion resistance are insufficient, and problems occur that make it difficult to use for boiling and retort packaging.
[0052] When a curing agent is used in the coating layer, an isocyanate curing system is preferred from the viewpoint of the heat resistance of the film, since it is a coating on a film, and in this case the resin component of the coating material must be polyester polyol. On the other hand, when an epoxy compound is used as a curing agent, it must be polyester polycarboxylic acid. In these cases, the coating layer becomes a crosslinked system, which has the advantage of improving heat resistance, abrasion resistance, and rigidity. Therefore, it is easy to use for boiling and retort packaging. On the other hand, there are problems with this, such as the liquid not being reusable after mixing with the curing agent, and the need for a curing (aging) process after coating.
[0053] When the polyester has a hydroxyl group, the polyisocyanate compound used in the present invention reacts at least partially to form a urethane structure, which makes the resin component highly polar, and the polymer chains are aggregated to further strengthen the gas barrier function. In addition, when the resin of the coating material is a straight-chain resin, crosslinking with a trivalent or higher polyisocyanate can impart heat resistance and abrasion resistance. The polyisocyanate compound used in the present invention may be any of diisocyanates, trivalent or higher polyisocyanates, low molecular weight compounds, and high molecular weight compounds, but it is preferable to contain an aromatic ring or an aliphatic ring in a part of the skeleton from the viewpoint of improving the gas barrier function. For example, examples of isocyanates having an aromatic ring include toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, and naphthalene diisocyanate; examples of isocyanates having an aliphatic ring include hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, isophorone diisocyanate, norbornine diisocyanate, or trimers of these isocyanate compounds; and compounds containing terminal isocyanate groups obtained by reacting an excess amount of these isocyanate compounds with low molecular weight active hydrogen compounds such as ethylene glycol, propylene glycol, trimethylolpropane, glycerin, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, and triethanolamine, or high molecular weight active hydrogen compounds such as various polyester polyols, polyether polyols, and polyamides.
[0054] [Inorganic thin film layer] The laminated film of the present invention may have an inorganic thin film layer on the surface of the coating layer. The inorganic thin film layer is a thin film made of a metal or an inorganic oxide. There is no particular limitation on the material for forming the inorganic thin film layer as long as it can be made into a thin film, but from the viewpoint of gas barrier properties, preferred examples include inorganic oxides such as silicon oxide (silica), aluminum oxide (alumina), and a mixture of silicon oxide and aluminum oxide. In this composite oxide, the mixing ratio of silicon oxide and aluminum oxide is preferably in the range of 20 to 70 mass% Al in terms of the mass ratio of the metal content. If the Al concentration is less than 20 mass%, the water vapor barrier properties may be reduced. On the other hand, if it exceeds 70 mass%, the inorganic thin film layer tends to become hard, and there is a risk that the film will be destroyed during secondary processing such as printing and lamination, resulting in a decrease in gas barrier properties. In addition, when the Al concentration is 100 mass%, the water vapor barrier performance is good, but since it is a single material, the surface tends to be smooth, and the slipperiness is poor and processing defects (wrinkles, acne, etc.) are likely to occur. Note that silicon oxide here refers to SiO or SiO 2 Aluminum oxide is AlO or Al 2 O 3 and mixtures thereof.
[0055] The inorganic thin film layer has a thickness of usually 1 to 100 nm, preferably 5 to 50 nm. If the inorganic thin film layer has a thickness of less than 1 nm, it may be difficult to obtain satisfactory gas barrier properties, while if the inorganic thin film layer has a thickness exceeding 100 nm, the corresponding improvement in gas barrier properties cannot be obtained, and it is rather disadvantageous in terms of flex resistance and production costs.
[0056] [Protective layer] In the present invention, when gas barrier performance is required or processing such as printing is required, a protective layer can be provided on the inorganic thin film layer. The inorganic thin film layer is not a completely dense film, but has minute missing parts scattered therein. By forming a protective layer by applying a specific resin composition for protective layer described later on the inorganic thin film layer, the resin in the resin composition for protective layer penetrates the missing parts of the inorganic thin film layer, resulting in an effect of stabilizing the gas barrier property. In addition, by using a material having gas barrier property for the protective layer itself, the gas barrier property of the laminated film is also greatly improved. However, it is necessary to note that the provision of the protective layer increases the number of processes, resulting in an increase in cost, and that depending on the material used, it may cause a burden on the environment. It is also necessary to note that the physical properties such as surface roughness change depending on the protective layer.
[0057] The amount of protective layer applied is 0.10 to 1.00 g / m 2 This allows the protective layer to be uniformly controlled during coating, resulting in a film with fewer coating irregularities and defects. In addition, the cohesive force of the protective layer itself is improved, and the adhesion between the inorganic thin film layer and the protective layer is also strengthened. The protective layer has a coating weight of 1.00 g / m 2 If the thickness of the protective layer exceeds 0.10 g / m, the gas barrier properties will improve, but the cohesive force inside the protective layer will be insufficient and the uniformity of the protective layer will also decrease, resulting in unevenness or defects in the coat appearance and insufficient gas barrier properties and adhesiveness. 2 If it is less than this, there is a risk that sufficient gas barrier properties and interlayer adhesion cannot be obtained.
[0058] Examples of the resin composition used for the protective layer formed on the surface of the inorganic thin film layer of the laminate film of the present invention include resins such as vinyl alcohol-based, urethane-based, polyester-based, acrylic-based, titanium-based, isocyanate-based, imine-based, and polybutadiene-based resins to which curing agents such as epoxy-based, isocyanate-based, and melamine-based curing agents have been added.
[0059] [Laminated film] The laminated film of the present invention is preferably a biaxially oriented film, and has a three-layer structure of coating layer / surface layer (B) / substrate layer (A), but may also have a four-layer structure of coating layer / surface layer (B) / substrate layer (A) / surface layer (C), a five-layer structure of coating layer / surface layer (B) / substrate layer (A) / intermediate layer (D) / surface layer (C), or a multilayer structure of more than one. When there are multiple substrate layers (A), surface layers (B), and surface layers (C), the compositions may be different as long as each layer satisfies its characteristics.
[0060] The total thickness of the laminated film of the present invention is preferably 9 μm or more and 200 μm or less, more preferably 10 μm or more and 150 μm or less, further preferably 12 μm or more and 100 μm or less, and particularly preferably 15 μm or more and 80 μm or less.
[0061] The ratio of the thickness of the surface layer (C) to the thickness of the base layer (A) in the laminated film of the present invention, i.e., the ratio of the thickness of the total surface layer (C) to the thickness of the total base layer (A), is preferably 0.01 to 0.50, more preferably 0.02 to 0.40, even more preferably 0.03 to 0.30, and particularly preferably 0.04 to 0.20. If the ratio of the total surface layer (C) to the total base layer (A) exceeds 0.50, the haze increases and the transparency deteriorates depending on the amount of the antiblocking agent added.
[0062] The thickness of the entire base layer (A) relative to the thickness of the entire film is preferably 50% or more and 99% or less, more preferably 60% or more and 97% or less, particularly preferably 70% or more and 95% or less, and most preferably 80% or more and 92% or less.
[0063] The haze of the laminated film of the present invention is preferably 5% or less, more preferably 0.2% or more and 5.0% or less, even more preferably 0.3% or more and 4.5% or less, and particularly preferably 0.4% or more and 4.0% or less. When the haze is within the above range, it may be easy to use in applications where transparency is required. For example, the haze tends to deteriorate when the stretching temperature or heat setting temperature is too high, the cooling roll temperature is high and the cooling rate of the unstretched (raw) sheet is slow, or there is too much low molecular weight component, and the haze can be adjusted to within the above range by adjusting these.
[0064] The Martens hardness of the coating layer side of the laminated film of the present invention preferably satisfies (a) / (b)≦7, where (a) is the Martens hardness measured at a test force of 0.1 mN, and (b) is the Martens hardness measured at 7 mN. The Martens hardness indicates the hardness of a resin when a needle tip with a curvature radius of 0.1 μm or less is pressed into the surface by about 0.1 to 2 μm using a dynamic ultra-microhardness tester. When measured at a test force of 0.1 mN, it indicates the Martens hardness of the coating layer, and when measured at a test force of 7 mN, it indicates the Martens hardness including the substrate film. When the ratio of these hardnesses (a) / (b) is 7 or less, the followability increases when physical deformation such as peeling occurs in the substrate film or the coating layer, and the adhesion strength improves. The preferred range of the ratio of Martens hardness (a) and (b) is (a) / (b)≦7.00, more preferably (a) / (b)≦6.00, and even more preferably (a) / (b)≦4.00. On the other hand, if (a) / (b) is 0.15 or less, the substrate film is too hard, and the coating layer cannot be formed well, which may cause unevenness or cracks. Therefore, the preferred lower limit of (a) / (b) is 0.15≦(a) / (b), more preferably 0.17≦(a) / (b), and even more preferably 0.25≦(a) / (b). In addition, the Martens hardness (a) is 80N / mm 2 More than 350N / mm 2 It is preferable that the resistance is less than 100 N / mm 2 More than 330N / mm 2 Martens hardness (b) is 55N / mm 2 More than 250N / mm2 It is preferable that the resistance is equal to or less than 70 N / mm 2 More than 230N / mm 2 The following is the result. In order to satisfy (a) / (b)≦7.00, it is possible to add ethylene and / or an α-olefin having 4 or more carbon atoms, or other copolymer components when forming the surface layer (B). It is also possible to lower the Martens hardness by lowering the stretching ratio of the film and decreasing the orientation of the molecular chain. Note that care must be taken because the drying heat when forming the coating layer and the radiant heat when forming the inorganic thin film layer can embrittle the film and change its hardness, or components derived from the base material can bleed out and harden it.
[0065] The sum of the maximum peak height (Rp) and maximum valley depth (Rv) of the surface of the coating layer side of the laminated film of the present invention measured by a scanning probe microscope (AFM) is preferably 0.1 nm or more and 30.0 nm or less. The maximum peak height (Rp) and maximum valley depth (Rv) are determined in accordance with the definitions described in JIS-B0601 (1994) by using a scanning probe microscope (AFM) in dynamic mode to measure in the range of 2 μm in both the X and Y directions, and correcting the obtained images (tilt, line fit, noise line removal).
[0066] The maximum peak height (Rp) and maximum valley depth (Rv) in a 2 μm square range measured by AFM are indicators of relatively large peaks and valleys formed by antiblocking agents and lubricants, and when laminating an inorganic thin film layer on the surface of the coating layer, the unevenness may cause poor formation of the inorganic thin film layer or induce cracks. If the sum of the maximum peak height (Rp) and maximum valley depth (Rv) exceeds 30.0 nm, the surface unevenness is large, and holes occur during the formation of the inorganic thin film, resulting in poor barrier properties. The sum of the maximum peak height (Rp) and maximum valley depth (Rv) on the coating layer side surface is more preferably 20.0 nm or less, even more preferably 10.0 nm or less, and most preferably 7.0 nm or less.
[0067] The laminated film of the present invention has an oxygen permeability of 1200 cc / m under conditions of 23°C x 65% RH. 2It is preferable that the viscosity is 1000 cc / m or less in order to exhibit good gas barrier properties when an inorganic thin film layer is laminated thereon. 2 / d / atm or less, more preferably 800cc / m 2 / d / atm or less. Oxygen permeability is 1200cc / m 2 If the oxygen permeability exceeds 100cc / m2, it becomes difficult to meet the requirements for high gas barrier properties when an inorganic thin film is laminated. 2 / d / atm or more. Oxygen permeability is 100cc / m 2 If the oxygen permeability is less than 100cc / m2, the barrier performance is excellent when an inorganic thin film layer is laminated, but the residual solvent is less likely to permeate to the outside of the bag, and the amount of migration to the contents may increase relatively, which is not preferable. 2 / d / atm or more, preferably 200cc / m 2 / d / atm or more, more preferably 300cc / m 2 / d / atm or more.
[0068] The laminated film of the present invention has a water vapor permeability of 10.0 g / m under conditions of 40°C x 90% RH. 2 It is preferable that the thickness is 8.0 g / m or less in order to exhibit good gas barrier properties when an inorganic thin film layer is laminated thereon. 2 / d or less, more preferably 7.0 g / m 2 / d or less. The water vapor permeability is 10.0 g / m 2 If the water vapor permeability exceeds 1.0 g / m / d, it becomes difficult to meet the requirements for applications requiring high gas barrier properties when an inorganic thin film is laminated. 2 If the water vapor permeability is less than 1.0 g / m2, the barrier performance is excellent, but the residual solvent is less likely to permeate to the outside of the bag, and the amount of the solvent that migrates to the contents is likely to increase. 2 / d or more.
[0069] When an inorganic thin film layer is laminated on the laminated film of the present invention, the oxygen permeability under the conditions of 23°C x 65% RH is 15cc / m 2 / d / atm or less, more preferably 12cc / m 2 / d / atm or less, more preferably 10cc / m 2 The preferred lower limit of oxygen permeability is 0.1 cc / m 2 / d / atm or more. In addition, the water vapor transmission rate under the conditions of 40℃ × 90% RH is 3.0g / m 2 / d or less. More preferably, it is 2.5 g / m 2 / d or less, more preferably 2.0 g / m 2 The preferred lower limit of the water vapor permeability is 0.1 g / m 2 / d or more.
[0070] [Laminate] When the laminated film of the present invention is used as a packaging material, it is preferable to form a laminate having a heat-sealable resin layer called a sealant. The heat-sealable resin layer is usually provided on the coating layer or inorganic thin film layer side, but may also be provided on the outside of the base film layer (the surface opposite to the surface on which the inorganic thin film is formed). The heat-sealable resin layer is usually formed by extrusion lamination or dry lamination. The thermoplastic polymer forming the heat-sealable resin layer may be any polymer capable of sufficiently exhibiting sealant adhesion, and may be, for example, polyethylene resins such as olefin-based HDPE, LDPE, and LLDPE, polypropylene resins, ethylene-vinyl acetate copolymers, ethylene-α-olefin random copolymers, and ionomer resins. Among these, LLDPE or polypropylene resins, which are highly versatile in terms of durability, seal strength, cost, and mono-materialization, are particularly preferable. The thickness of the sealant layer is preferably 20 to 100 μm, more preferably 30 to 90 μm, and even more preferably 40 to 80 μm. If the thickness is less than 20 μm, sufficient seal strength may not be obtained, or the sealant may lack stiffness and be difficult to handle. On the other hand, if the thickness exceeds 100 μm, the bag will feel stiff and will be difficult to handle, and the price may also become high.
[0071] The laminate of the present invention preferably has a laminate strength of 1.0 N / 15 mm or more under 23°C x 65% RH conditions in both dry and wet evaluations described below, more preferably 1.5 N / 15 mm or more, and even more preferably 2.0 N / 15 mm or more. If the laminate strength is less than 1.0 N / 15 mm, peeling may occur due to bending load or heat during sealing, resulting in deterioration of barrier properties or leakage of contents. Furthermore, hand tearability may also be deteriorated.
[0072] [Adhesive layer] The adhesive layer used in the present invention can be a general-purpose adhesive for lamination. For example, (non-)solvent, water-based, or hot melt adhesives mainly composed of poly(ester)urethane, polyester, polyamide, epoxy, poly(meth)acrylic, polyethyleneimine, ethylene-(meth)acrylic acid, polyvinyl acetate, (modified) polyolefin, polybutadiene, wax, or casein can be used. Among these, urethane or polyester adhesives are preferred in consideration of heat resistance and flexibility that can follow dimensional changes of each substrate. The adhesive layer can be applied by, for example, direct gravure coating, reverse gravure coating, kiss coating, die coating, roll coating, dip coating, knife coating, spray coating, fountain coating, or other methods, and the coating amount after drying is 1 to 8 g / m in order to develop sufficient adhesion. 2 More preferably, the thickness is 2 to 7 g / m 2 , and more preferably 3 to 6 g / m 2 The coating amount is 1g / m 2 If it is less than 8g / m, it becomes difficult to bond the entire surface, and the adhesive strength decreases. 2 If the temperature exceeds this range, it will take a long time for the film to completely cure, unreacted material will be likely to remain, and adhesive strength will decrease.
[0073] [Print layer] Furthermore, in the laminate film of the present invention, at least one printed layer or other plastic substrate and / or paper substrate may be laminated between the substrate film layer and the heat-sealable resin layer or on the outer side thereof.
[0074] As the printing ink for forming the printing layer, water-based and solvent-based resin-containing printing inks can be preferably used. Examples of the resin used in the printing ink include acrylic resins, urethane resins, polyester resins, vinyl chloride resins, vinyl acetate copolymer resins, and mixtures thereof. The printing ink may contain known additives such as antistatic agents, light blocking agents, ultraviolet absorbers, plasticizers, lubricants, fillers, colorants, stabilizers, lubricants, defoamers, crosslinking agents, anti-blocking agents, and antioxidants. The printing method for providing the printing layer is not particularly limited, and known printing methods such as offset printing, gravure printing, and screen printing can be used. To dry the solvent after printing, known drying methods such as hot air drying, hot roll drying, and infrared drying can be used.
[0075] Manufacturing method [Base film] The polypropylene-based laminated film of the present invention is preferably a biaxially oriented film, and can be obtained by melt-extruding the polypropylene-based resin composition constituting the base layer (A), the polypropylene-based resin composition constituting the surface layer (B), and the polypropylene-based resin composition constituting the surface layer (C) using separate extruders, co-extruding from a die, and cooling with a cooling roll to form an unstretched sheet, stretching the unstretched sheet in the machine direction (MD) and the transverse direction (TD), and then heat-setting the sheet. It is preferable to extrude the surface layer (B) so that the surface layer (B) is in contact with the cooling roll. If the surface layer (B) is on the opposite side to the surface that is in contact with the cooling roll, the polypropylene resin is slowly cooled, the crystallization degree is increased, and the arithmetic average roughness (Ra) of the surface of the surface layer (B) may be too large due to surface unevenness caused by spherulites. The melt extrusion temperature is preferably about 200 to 280°C. In order to obtain a laminated film with good appearance without disturbing the layers within this temperature range, it is preferable that the viscosity difference (MFR difference) between the polypropylene raw material for the base layer (A) and the polypropylene raw material for the surface layer (B) is 6.0 g / 10 min or less. If the viscosity difference is more than 6 g / 10 min, the layers are likely to be disturbed, resulting in poor appearance. The viscosity difference is more preferably 5.5 g / 10 min or less, and even more preferably 5.0 g / 10 min or less.
[0076] The surface temperature of the cooling roll is preferably 25 to 35° C., more preferably 27 to 33° C. If the cooling roll temperature exceeds 35° C., the degree of crystallinity of the polypropylene resin increases, and the arithmetic mean roughness (Ra) of the surface of the surface layer (B) may become too large due to surface irregularities caused by the formed spherulites.
[0077] The lower limit of the stretching ratio in the machine direction (MD) is preferably 3 times, more preferably 3.5 times. If it is less than the above, the film thickness may become uneven. The upper limit of the stretching ratio in the MD is preferably 8 times, more preferably 7 times. If it exceeds the above, the subsequent TD stretching may become difficult. The lower limit of the MD stretching temperature is preferably 120 ° C, more preferably 125 ° C, and even more preferably 130 ° C. If it is less than the above, the mechanical load may become large, the thickness unevenness may become large, and the surface of the film may become rough. The upper limit of the MD stretching temperature is preferably 160 ° C, more preferably 155 ° C, and even more preferably 150 ° C. A higher temperature is preferable for reducing the heat shrinkage rate, but it may adhere to the roll, making it impossible to stretch, or the surface may become rough.
[0078] The lower limit of the stretching ratio in the transverse direction (TD) is preferably 4 times, more preferably 5 times, and even more preferably 6 times. If it is less than the above, thickness unevenness may occur. The upper limit of the TD stretching ratio is preferably 20 times, more preferably 17 times, even more preferably 15 times, and particularly preferably 12 times. If it exceeds the above, the heat shrinkage rate may increase or the film may break during stretching. The preheating temperature in TD stretching is preferably set to be 5 to 15°C higher than the stretching temperature in order to quickly raise the film temperature to the vicinity of the stretching temperature. The lower limit of the TD stretching temperature is preferably 150°C, more preferably 155°C, even more preferably 158°C, and especially preferably 160°C. If it is less than the above, the film may break due to insufficient softening, or the heat shrinkage rate may increase. The upper limit of the TD stretching temperature is preferably 170°C, more preferably 168°C, and even more preferably 165°C. To reduce the heat shrinkage rate, a higher temperature is preferable, but if the temperature exceeds the above range, the low molecular weight components will melt and recrystallize, causing not only a decrease in orientation but also surface roughness and whitening of the film.
[0079] The stretched film is heat set. The lower limit of the heat setting temperature is preferably 163°C, more preferably 165°C. If the temperature is lower than the above, the heat shrinkage rate may be high. In addition, a long period of treatment may be required to reduce the heat shrinkage rate, which may result in poor productivity. The upper limit of the heat setting temperature is preferably 176°C, more preferably 175°C. If the temperature exceeds the above range, low molecular weight components may melt and recrystallize, causing surface roughness and whitening of the film.
[0080] It is preferable to relax the film during heat setting. The lower limit of the relaxation rate is preferably 2%, more preferably 3%. If it is less than the above, the thermal shrinkage rate may be high. The upper limit of the relaxation rate is preferably 10%, more preferably 8%. If it exceeds the above, the thickness unevenness may become large.
[0081] Furthermore, in order to reduce the thermal shrinkage rate, the film produced by the above process may be wound into a roll and then annealed offline.
[0082] The biaxially oriented polypropylene laminate film thus obtained can be subjected to corona discharge, plasma treatment, flame treatment, etc., as necessary, and then wound up with a winder to obtain the biaxially oriented polypropylene film roll of the present invention.
[0083] [Coating layer] The coating method of the resin composition for the coating layer is not particularly limited as long as it is a method that coats the film surface to form a layer. For example, a typical coating method such as gravure coating, reverse roll coating, wire bar coating, die coating, etc. can be used.
[0084] When forming the coating layer, it is preferable to apply the resin composition for the coating layer and then heat-dry it. The drying temperature is preferably 100 to 180 ° C, more preferably 110 to 170 ° C, and even more preferably 130 to 160 ° C. If the drying temperature is less than 110 ° C, the coating layer may not be sufficiently dried, or the film formation of the coating layer may not proceed, resulting in a decrease in cohesive strength and water-resistant adhesion, and as a result, the barrier properties and hand-cutting properties may decrease. On the other hand, if the drying temperature exceeds 190 ° C, the film may be too hot, making it brittle and reducing the puncture strength, or shrinking and causing poor processability. In particular, by drying at 130 ° C or higher, the film formation of the coating layer can proceed effectively and the water-resistant adhesion can be improved. It is particularly preferable to first volatilize the solvent at a relatively low temperature condition of 90 ° C to 110 ° C immediately after application, and then dry at 130 ° C or higher, since a uniform film can be obtained. In addition to drying, additional heat treatment at a temperature as low as possible is also effective in accelerating the formation of the coating layer.
[0085] [Inorganic thin film layer] The method for forming the inorganic thin film layer is not particularly limited, and any known deposition method may be appropriately used, for example, a physical deposition method (PVD method) such as a vacuum deposition method, a sputtering method, or an ion plating method, or a chemical deposition method (CVD method). A typical method for forming an inorganic thin film layer will be described below using a silicon oxide / aluminum oxide thin film as an example. For example, when the vacuum deposition method is used, SiO 2 and Al 2 O 3 or a mixture of SiO 2 A mixture of ZnO and Al is preferably used. Particles are usually used as the deposition raw materials, and in this case, the size of each particle is desirably large enough that the pressure during deposition does not change, and the preferred particle diameter is 1 mm to 5 mm. Heating can be performed by resistance heating, high-frequency induction heating, electron beam heating, laser heating, or other methods. It is also possible to introduce oxygen, nitrogen, hydrogen, argon, carbon dioxide, water vapor, or other reactive gases as reactive gases, or to employ reactive deposition using ozone addition, ion assist, or other means. Furthermore, the film formation conditions can be changed arbitrarily, such as by applying a bias to the deposition target (laminated film to be subjected to deposition), or by heating or cooling the deposition target. Such deposition materials, reactive gases, bias, heating and cooling of the deposition target, etc. can be changed in the same way when the sputtering method or CVD method is used.
[0086] [Protective layer] The method of coating the resin composition for the protective layer is not particularly limited as long as it is a method that coats the film surface to form a layer. For example, a typical coating method such as gravure coating, reverse roll coating, wire bar coating, or die coating can be used.
[0087] When forming a protective layer, it is preferable to apply the resin composition for the protective layer and then heat-dry it. The drying temperature is preferably 100 to 160°C, more preferably 105 to 155°C, and even more preferably 110 to 150°C. If the drying temperature is less than 100°C, the protective layer may be insufficiently dried, or the film formation of the protective layer may not proceed, resulting in a decrease in cohesive strength and water-resistant adhesion, and as a result, the barrier properties and hand-tearability may decrease. On the other hand, if the drying temperature exceeds 160°C, the film may be too hot, making it brittle and reducing the puncture strength, or shrinking and causing poor processability. In particular, by drying at 100°C or higher, preferably 110°C or higher, the film formation of the protective layer progresses effectively, and the adhesive area between the resin of the protective layer and the inorganic thin film layer becomes larger, thereby improving the water-resistant adhesion. It is particularly preferable to first volatilize the solvent at a relatively low temperature of about 90°C immediately after application, and then dry at 100°C or higher, since a uniform film can be obtained. In addition to drying, additional heat treatment at a temperature as low as possible is also effective in accelerating the formation of the protective layer. EXAMPLES
[0088] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to the following examples. The films were evaluated by the following measurement methods.
[0089] [Measurement method] (1) Thickness (μm) The thickness of each layer was measured by cutting out a cross section of the laminate film of the present invention solidified with a modified urethane resin using a microtome and observing it under a differential interference microscope.
[0090] (2) Martens hardness (N / mm 2 ) The obtained laminated film was cut into approximately 2 cm squares, and the surface opposite to the coating layer side (measurement surface) was fixed with an adhesive on a glass plate with a thickness of approximately 1 mm, and then left in an atmosphere of 23°C and 50% RH for 12 hours to condition the humidity. This sample was measured using a dynamic ultra-microhardness tester (Shimadzu Corporation's "DUH-211") under the following measurement conditions according to the method of ISO14577-1 (2002). The measurement was performed 10 times by changing the position of the film, and the average value of 8 points excluding the maximum and minimum was calculated.
[0091] <Measurement conditions> (setting) Measurement environment: Temperature 23°C, relative humidity 50% Test mode: Load-unload test ·Indenter used: ridge angle 115 degrees, triangular pyramid indenter Indentation modulus: 1.140×106N / mm 2 Indenter Poisson's ratio: 0.07 Cf-Ap,As correction: Yes (Condition a) Test force: 0.10mN ·Load speed: 0.0050mN / sec ·Load holding time: 5sec ·Unloading holding time: 0sec (condition b) Test force: 7.00mN ·Load speed: 1.4632mN / sec ·Load holding time: 5sec ·Unloading holding time: 0sec.
[0092] (3) Maximum peak height (Rp) and maximum valley depth (Rv) (nm) The maximum peak height (Rp) and maximum valley depth (Rv) of the coating layer side of the obtained laminated film were measured using a scanning probe microscope (Shimadzu Corporation "SPM-9700") in dynamic mode. Measurements were performed in the range of 2 μm in both the X and Y directions, and the obtained images were corrected (tilt, line fit, noise line removal) and then calculated according to the definitions described in JIS-B0601 (1994).
[0093] (4) Coating layer adhesion In each of the Examples and Comparative Examples, each laminate film obtained at the stage of laminating the coating layer on the base film was used as a sample, and a test piece of 100 mm x 100 mm was cut out from this sample, and the coating layer was wiped off with acetone. The amount of adhesion was calculated from the change in mass of the film before and after wiping.
[0094] (5) Composition and thickness of inorganic thin film layer The film thickness composition of the laminated films (after thin film lamination) obtained in the examples and comparative examples was measured using a fluorescent X-ray analyzer ("ZSX100e" manufactured by Rigaku Corporation) based on a calibration curve prepared in advance. The excitation X-ray tube conditions were 50 kV and 70 mA.
[0095] (6) Evaluation method for laminate strength The laminated laminate prepared by the method described below was cut into a test piece with a width of 15 mm and a length of 200 mm, and the laminate strength was measured using a Tensilon universal material testing machine ("Tensilon UMT-II-500" manufactured by Toyo Baldwin Co., Ltd.) under the conditions of a temperature of 23°C and a relative humidity of 65%. The laminate strength was measured at a tensile speed of 200 mm / min, the laminated film layer and the heat-sealable resin layer of each laminated film obtained in the examples and comparative examples were peeled off at a peeling angle of 90 degrees, and the strength was measured when water was dripped on the peeled part with a dropper (watered) and when it was not dripped (dry).
[0096] (7) Evaluation method for oxygen permeability In each of the Examples and Comparative Examples, a laminate film or laminated body described below was used as a sample, and the oxygen permeability was measured in accordance with JIS-K7126 Method B using an oxygen permeability measuring device ("OX-TRAN (registered trademark) 1 / 50" manufactured by MOCON) under an atmosphere of temperature 23°C and humidity 65% RH. The oxygen permeability was measured in the direction in which oxygen permeates from the surface layer (C) side.
[0097] (8) Method for evaluating water vapor permeability In each of the Examples and Comparative Examples, a laminate film or laminated body described below was used as a sample, and the water vapor permeability was measured in an atmosphere at a temperature of 40° C. and a humidity of 90% RH using a water vapor permeability measuring device ("PERMATRAN-W 3 / 33MG" manufactured by MOCON) in accordance with JIS-K7129 Method B. The water vapor permeability was measured in the direction in which water vapor permeates from the surface layer (C) side.
[0098] (8) Appearance evaluation method In each of the Examples and Comparative Examples, after laminating the coating layer, the appearance of the surface on the coating layer side was visually evaluated. ○: No defects, good ×: Any of the following defects occurs: wrinkles, uneven coating, or repelling
[0099] [Preparation of base film] (OPP-1) For the base layer (A), a polypropylene homopolymer PP-1 shown in Table 1 was used. For the surface layer (B), 43.2% by weight of polypropylene homopolymer PP-2 shown in Table 1, 52.0% by weight of ethylene copolymerized polypropylene polymer PP-4 shown in Table 1, and 4.8% by weight of antiblocking agent-containing master batch FTX0627G were used. At this time, the melt flow rate (g / 10 min) of the polypropylene resin composition constituting the surface layer (B) was 5.1. For the surface layer (C), a mixture of 93.6% by weight of polypropylene homopolymer PP-1 shown in Table 1 and 6.4% by weight of antiblocking agent-containing master batch FTX0627G was used. The base layer (A) was made using a 45 mm extruder, the surface layer (B) was made using a 25 mm extruder, and the surface layer (C) was made using a 20 mm extruder. The raw material resins were melted at 250 ° C. and co-extruded from a T-die into a sheet shape, and the surface layer (B) was cooled and solidified so that it contacted a cooling roll at 30 ° C., and then stretched 4.5 times in the machine direction (MD) at 135 ° C. Then, in a tenter, both ends of the film in the width direction (TD) were clamped with clips, preheated at 173 ° C., stretched 8.2 times in the width direction (TD) at 164 ° C., and heat-set at 171 ° C. while relaxing 6.7% in the width direction (TD). The film formation conditions at this time were film formation conditions a. In this way, a biaxially oriented polypropylene film having a structure of surface layer (B) / base layer (A) / surface layer (C) was obtained. The surface of the surface layer (B) of the biaxially oriented polypropylene film was corona-treated using a corona treatment machine manufactured by Softal Corona & Plasma GmbH at an applied current value of 0.75 A, and then wound up with a winder. The thickness of the obtained film was 20 μm (thickness of surface layer (B) / base layer (A) / surface layer (C) was 1.3 μm / 17.7 μm / 1.0 μm).
[0100] (OPP-2) The base layer (A) was made of 99.0% by weight of the polypropylene homopolymer PP-2 shown in Table 1 and 1.0% by weight of stearyl diethanolamine stearate (KYM-4K, Matsumoto Oil Co., Ltd.) as an antistatic agent. For the surface layer (B), 43.2% by weight of polypropylene homopolymer PP-2 shown in Table 1, 52.0% by weight of ethylene copolymerized polypropylene polymer PP-4 shown in Table 1, and 4.8% by weight of antiblocking agent-containing master batch FTX0627G were used. At this time, the melt flow rate (g / 10 min) of the polypropylene resin composition constituting the surface layer (B) was 5.1. For the surface layer (C), a mixture of 93.6% by weight of polypropylene homopolymer PP-2 and 6.4% by weight of antiblocking agent-containing master batch FTX0627G shown in Table 1 was used. The base layer (A) was made using a 45 mm extruder, the surface layer (B) was made using a 25 mm extruder, and the surface layer (C) was made using a 20 mm extruder. The raw material resins were melted at 250 ° C. and co-extruded from a T-die into a sheet shape, and the surface layer (B) was cooled and solidified so that it contacted a cooling roll at 30 ° C., and then stretched 4.5 times in the machine direction (MD) at 125 ° C. Then, in a tenter, both ends of the film in the width direction (TD) were clamped with clips, preheated at 168 ° C., stretched 8.2 times in the width direction (TD) at 155 ° C., and heat-set at 165 ° C. while relaxing 6.7% in the width direction (TD). The film formation conditions at this time were film formation conditions b. In this way, a biaxially oriented polypropylene film having a structure of surface layer (B) / base layer (A) / surface layer (C) was obtained. The surface of the surface layer (B) of the biaxially oriented polypropylene film was corona-treated using a corona treatment machine manufactured by Softal Corona & Plasma GmbH at an applied current value of 0.75 A, and then wound up with a winder. The thickness of the obtained film was 20 μm (thickness of surface layer (B) / base layer (A) / surface layer (C) was 1.3 μm / 17.7 μm / 1.0 μm).
[0101] (OPP-3) A 20 μm biaxially oriented polypropylene film was obtained under the same conditions as OPP-2, except that the polypropylene homopolymer PP-2 used in the base layer (A) of OPP-2 was changed to 100% by weight.
[0102] (OPP-4) For the base layer (A), a blend of 60.0% by weight of polypropylene homopolymer PP-2 and 40.0% by weight of PP-3 shown in Table 1 was used. For the surface layer (B), a mixture of 96.4% by weight of polypropylene homopolymer PP-2 and 3.6% by weight of antiblocking agent-containing master batch FTX0627G shown in Table 1 was used. For the surface layer (C), a mixture of 94.0% by weight of the polypropylene homopolymer PP-2 shown in Table 1 and 6.0% by weight of the antiblocking agent-containing master batch FTX0627G was used. The film-forming conditions were as shown in Table 3 (b), and a biaxially oriented polypropylene film having a structure of surface layer (B) / base layer (A) / surface layer (C) was obtained. The surface of the surface layer (B) of the biaxially oriented polypropylene film was corona-treated using a corona treatment machine manufactured by Softal Corona & Plasma GmbH at an applied current value of 0.75 A, and then wound up with a winder. The thickness of the obtained film was 20 μm (thickness of surface layer (B) / base layer (A) / surface layer (C) was 1.0 μm / 18.0 μm / 1.0 μm).
[0103] [Creation of coating layer] The method for producing the coating layer used in each of the Examples and Comparative Examples will be described below.
[0104] [Coating fluid 1] A solution of 0.25 parts by mass of silane coupling agent (I); "DF-ADDITIVE AES" manufactured by DIC Corporation dissolved in 1.43 parts by mass of acetone was mixed with 3.74 parts by mass of isocyanate (II); "DF-HARDNER HX-75" manufactured by DIC Corporation and stirred for 10 minutes using a magnetic stirrer. The resulting mixture was diluted with 72.06 parts by mass of methyl ethyl ketone and 12.72 parts by mass of 1-methoxy-2-propanol (hereinafter PGM), and 9.80 parts by mass of polyester resin (III); "DF-COAT GEC-004C" manufactured by DIC Corporation was added to obtain the target coating solution 1.
[0105] [Coating fluid 2] To 90 parts by mass of purified water, 10 parts by mass of fully saponified polyvinyl alcohol resin (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name: G Polymer OKS8049Q, (saponification degree 99.0% or more, average polymerization degree 450) was added, and the mixture was heated to 80°C with stirring, and then stirred for about 1 hour. The mixture was then cooled to room temperature, thereby obtaining a nearly transparent polyvinyl alcohol solution (PVA solution) with a solids content of 10%. 50.00 parts by mass of the above PVA solution was mixed with a mixed solution of 35.00 parts by mass of purified water and 15.00 parts by mass of 2-propanol, to obtain the target coating solution 2.
[0106] [Coating fluid 3] To a mixed solution of 53.20 parts by mass of purified water and 22.80 parts by mass of 2-propanol, 24.00 parts by mass of WPB-531 manufactured by Mitsui Chemicals was added and stirred to obtain the intended coating solution 3.
[0107] [Making laminated films] (Examples 1 and 2) OPP-1 was used for the base film, and coating solution 1 was used for the coating layer. The corona-treated surface of the base film was coated with the coating solution by gravure roll coating, pre-dried at 100°C, and then dried at 130°C. The coating layer had a deposition weight of 0.80 g / m 2 Thereafter, a post-heat treatment was carried out at 40° C. for 2 days to obtain the desired laminated film. Example 3 The target laminated film was obtained under the same conditions as in Example 1, except that the base film was changed to OPP-2. Example 4 The target laminated film was obtained under the same conditions as in Example 1, except that the base film was changed to OPP-3. Example 5 Coating weight of 0.20g / m 2 The target laminated film was obtained under the same conditions as in Example 1, except for changing the above. Example 6 Coating weight of 1.00g / m 2 The target laminated film was obtained under the same conditions as in Example 1, except for changing the above. Example 7 The target laminated film was obtained under the same conditions as in Example 1, except that the main drying was performed at 110°C. Example 8 The target laminated film was obtained under the same conditions as in Example 1, except that the main drying was performed at 150°C.
[0108] Comparative Example 1 OPP-1 was used for the base film, and no covering layer was laminated. Comparative Example 2 The target laminated film was obtained under the same conditions as in Example 1, except that the base film was changed to OPP-4. Comparative Example 3 The target laminated film was obtained under the same conditions as in Example 1, except that Coating Liquid 2 was used for the coating layer. Comparative Example 4 The target laminated film was obtained under the same conditions as in Example 1, except that Coating Liquid 3 was used for the coating layer. Comparative Example 5 Coating weight of 1.20g / m 2 The target laminated film was obtained under the same conditions as in Example 1, except for changing the above.
[0109] [Formation of inorganic thin film layer] The method for producing the inorganic thin film layer used in each of the Examples and Comparative Examples will be described below. (M-1: Example 2, Comparative Examples 1 and 3) As the inorganic thin film layer M-1, a composite oxide layer of silicon dioxide and aluminum oxide was formed on the coating layer by electron beam deposition. 2 (99.9% purity) and A1 2 O 3 (99.9% purity) was used. The inorganic thin film layer (SiO 2 / A1 2 O 3 The thickness of the composite oxide layer was 13 nm. The composition of this composite oxide layer was SiO 2 / A1 2 O 3 The mass ratio was 60 / 40.
[0110] (M-2; Examples 1, 3 to 8, Comparative Examples 2 and 4) Metallic aluminum was vapor-deposited on the coating layer to form the inorganic thin film layer M-2. Using a small vacuum deposition device (ULVAC KIKOU Co., Ltd., VWR-400 / ERH), the pressure was reduced to 10-3 Pa or less, and then aluminum foil with a purity of 99.9% was set on a Nilaco vapor deposition source CF-305W from below the substrate. Metallic aluminum was heated and evaporated, and deposited on the film to form a metallic aluminum film with a thickness of 40 nm.
[0111] [Preparation of laminated body] A polyurethane adhesive (TM569 / cat10L manufactured by Toyo-Morton Co., Ltd.) was applied onto the laminated films obtained in the Examples and Comparative Examples so that the thickness after drying treatment at 80°C would be 3 μm, and then an unstretched polypropylene film (P1128 manufactured by Toyobo Co., Ltd.; thickness 30 μm; referred to as CPP) was dry laminated thereon and aged at 40°C for 4 days to obtain a laminate for evaluation.
[0112] The laminated films and laminates were produced in the manner described above. The raw materials and production methods of the films used in the above examples and comparative examples are shown in Tables 1 to 3. In addition, the results of various evaluations of the obtained laminated films are shown in Table 4.
[0113] [Table 1]
[0114] [Table 2]
[0115] [Table 3]
[0116] [Table 4A]
[0117] [Table 4B] [Industrial Applicability]
[0118] According to the present invention, it is possible to provide a laminate film that can form a laminate structure composed of almost a single resin type, mainly consisting of a polypropylene film, which has a low environmental impact, and that, when laminated with an inorganic thin film layer, has the necessary gas barrier properties and adhesive properties required for packaging materials.
Claims
1. A laminate film comprising a substrate layer (A) made of a biaxially oriented polypropylene film, a surface layer (B) on at least one surface thereof, and a coating layer containing a urethane resin laminated on the surface layer (B), the laminate film being characterized in that the laminate film satisfies the following requirements (I) to (III): (I) When the Martens hardness measured on the surface on the coating layer side with a test force of 0.1 mN is (a) and the Martens hardness measured on the surface on the coating layer side with a test force of 7 mN is (b), the ratio (a) / (b) satisfies ≦7.
00. (II) The sum of the maximum peak height (Rp) and the maximum valley depth (Rv) measured on the coating layer side surface by a scanning probe microscope is 30.0 nm or less. (III) Water vapor permeability measured under conditions of 40°C x 90% RH is 1.0 g / m 2 / day or more, 10.0g / m 2 / day or less
2. 2. The laminate film according to claim 1, further comprising an inorganic thin film layer laminated on the coating layer of the laminate film.
3. The coating layer has a coating weight of 0.10 g / m 2 Above, 1.00g / m 2 3. The laminated film according to claim 1 or 2, characterized in that:
4. A laminate comprising the laminate film according to any one of claims 1 to 3 and an olefin-based sealant layer laminated on one side of the laminate film.
5. The laminate according to claim 4, wherein the laminate has a lamination strength of 1.0 N / 15 mm or more.
Citation Information
Patent Citations
Composite film and production thereof
JP1992359033A
Oxygen gas barrier film and method for manufacturing the same
JP2003145690A
Polypropylene based laminated film and gas-barrier film
JP2008132614A
Gas barrier laminated film
JP2011062977A
Decorative material for flooring
JP2012213913A